Meningkatkan Hasil Belajar Peserta Didik Melalui Model Project Based Learning (PjBL) Pada Materi Erosi Menggunakan Media Konkrit Tanah Di Kelas 5 - Laili Nurus Sa’adah; Jarmani Jarmani; Endang Supartin (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
The research was carried out with the aim of improving the learning outcomes of class V students at SDN Dukuh Kupang V Surabaya in science subjects through the Project Based Learning (PjBL) learning model. This research is classroom action research (PTK) which was carried out in two cycles. The subjects in this research were class V students at SDN Dukuh Kupang V, Surabaya City, totaling 28 students consisting of 13 male students and 15 female students. The data collection technique in this research is using pretest and posttest to measure student learning outcomes. Based on this research, it can be seen that student learning outcomes in science and science subjects have increased starting from pre-cycle with completeness by 14%, then in cycle I it has increased to 62% and in cycle II it has increased to 95%. The data was then analyzed using qualitative descriptive and quantitative descriptive methods. From cycle I to cycle II there was an increase of 33%. From calculating this data, it can be seen that the use of the Project Based Learning model can improve the learning outcomes of 5th grade elementary school students.